API, Cloud computing, WebGIS and cartography - Andrea Favretto (Netcom)
This paper explores some of the digital mapping processes available on the Internet in order to analyse their cartographic congruence. It will focus on WebGIS-based cartography in relation to what is produced using Mash-up site maps. These websites often use Googlebased maps in order to produce their own cartography. Thus, we can identify two main typologies of Internet mapping sites, which are characterized by the ownership or non-ownership of their cartographic bases. This paper will critically assess the cartography employed in the two different instances. A concise introduction to the Cloud Computing Internet propagated phenomenon is also premised in order to provide the reader with an accurate frame of reference. Cloud Computing has encouraged a significant Internet participation via the Application Programming Interface software (API), leading to mash-up cartographic websites.